(untitled) (Archives of Clinical and Medical Case Reports, 2019)
A sports hernia is an increasingly recognized cause of chronic groin pain among many professional and non-professional athlete. It is a misnomer as there is no classic herniation of soft tissue. However, small occult inguinal hernias are documented during surgical exploration. It is more commonly seen in young male than female athletes. Diagnosis is usually challenging as most this pain has an insidious onset. It requires a high index of suspicious as clinically visible sports hernia has not yet been reported in the English literature. Similarly, a visible incarcerated femoral hernia in a young weightlifter has yet to be reported. We report the case of 27 years young professional female weightlifter who presented with having an aching pain in her left groin for one year. She had visited many GP’s and her pain temporary subsided with the use of NSAIDs. A Computerized Tomography of abdomen and pelvis revealed a left femoral hernia. Emergency femoral hernia repair was performed. The patient’s had an uneventful post-op recovery. At 36 months follow up the patient is doing well, participating in her professional weightlifting without any further complaints. This case highlights the typical presentation of the sports hernia i.e chronic groin pain and also illustrates how the diagnosis of this hernia is missed or delayed. We hereby report the world first case of incarcerated visible femoral hernia in a young professional weightlifter and a literature search was performed to highlight its management options.